Urgensinya Implementasi Hubungan Agama dan Negara saat Ini (Studi Kasus Aek Kanopan, Kec. Kualuh Hulu, Kab. Labuhan Batu Utara) - Naufal Azis; Hani Salsabila; Kayla Aida Fitri; Fauziyah Br Pasaribu; Rifaldi Ritamil Sipahutar; Salwa Humaira Lubis; Nabila Mutiara (Jurnal Ilmu Agama Indonesia, 2026)
The relationship between religion and the state plays a vital role in shaping a harmonious and just society. In Indonesia, religion serves as a source of moral values, while the state is responsible for regulating communal life to achieve social order and welfare. Although the conceptual relationship between religion and the state is well-established, its practical implementation within society still faces various challenges. This study aims to determine how the relationship between religion and the state is understood and applied in the daily lives of the people in Kualuh Hulu, Aek Kanopan. This research employs a qualitative method with a descriptive approach through structured interviews with 40 respondents. The research instrument consists of closed-ended questions with the answer options "yes," "no," and "maybe/sometimes." The results indicate that the public generally understands the importance of the relationship between religion and the state; however, its implementation in social life is not yet fully consistent and remains situational.